Análise empírica da presença de 'Market timing' no mercado acionário brasileiro - Ferraz, Mauricio de Sousa (2009)
This paper examines the existence of market timing in the brazilian stock market. Our studies were divided in three separate analyses. We started looking for 'Market Timing' in the initial public offerings (IPOs) of brazilian firms and later we expanded our studies to the seasoned equity offerings (SEOs). To finish we studied the persistence of 'Market Timing' effects in the capital structure of the companies. Our findings show that brazilian companies issue more equity when the market is hot. This equity issues occur in the IPOs and SEOs and they change the capital structure of the companies. As time goes by, the change in the capital structure tends to reduce.